Soil Carbon Dioxide Emissions and Carbon Sequestration with Implementation of Alley Cropping in a Mediterranean Citrus Orchard - Jose A. Acosta; Alberto Imbernón-Mulero; Belén Gallego-Elvira; Jose F. Maestre-Valero; Silvia Martínez-Martínez; Victoriano Martínez-Álvarez (Plants, 2024)
Agroecological ecosystems produce significant carbon dioxide fluxes; however, the equilibrium of their carbon sequestration, as well as emission rates, faces considerable uncertainties. Therefore, sustainable cropping practices represent a unique opportunity for carbon sequestration, compensating greenhouse gas emissions. In this research, we evaluated the short-term effect of different management practices in alleys (tillage, no tillage, alley cropping with Rosmarinus officinalis and Thymus hyemalis on soil properties, carbon sequestration, and CO2 emissions in a grapefruit orchard under semiarid climate). For two years every four months, soil sampling campaigns were performed, soil CO2 emissions were measured, and rhizosphere soils were sampled at the end of the experimental period. The results show that alley cropping with Thymus and Rosmarinus contributed to improve soil fertility, increasing soil organic carbon (SOC), total nitrogen, cation exchange capacity, and nutrients. The CO2 emission rates followed the soil temperature/moisture pattern. Tillage did not contribute to higher overall CO2 emissions, and there were no decreased SOC contents. In contrast, alley crops increased CO2 emission rates, especially Rosmarinus; however, the bigger root system and biomass of Rosmarinus contributed to soil carbon sequestration at a greater rate than Thymus. Therefore, Rosmarinus is positioned as a better option than Thymus to be used as an alley crop, although long-term monitoring is required to evaluate if the reported short-term benefits are maintained over time.